Correlation between Ki-67 labeling index and mitotic index in Head and neck squamous cell carcinoma - Das C. K Deepa; Sunitha Balakrishnan (Indian Journal of Pathology and Microbiology)
Background: Proliferative activity of any tissue or neoplasm can be determined by its growth rate by mitotic count or by using antibodies directed against specific antigens like Ki-67. The usefulness of Ki-67 in head and neck cancers has been debated for the past 20 years; however, no study has definitively resolved this controversy. Aim: Assess the correlation between Ki-67 expression and mitotic index in head and neck squamous cell carcinoma. Materials and Methods: This cross-sectional study was performed in 66 histologically proven cases of Head and Neck Squamous cell carcinoma (SCC) received in a histopathology laboratory and satisfied the specified criteria. Tumor was graded. Mitotic and Ki67 labeling index was calculated. Statistical analysis was performed using appropriate techniques to determine the correlation coefficient. Results: A statistically significant difference in the Ki67 labeling index (LI) between the grades of the tumor proper was noted (P = 0.040). An increase in the mean mitotic index with histological grade was noted, which was statistically significant in the proliferating margin (P = 0.037). A statistically significant positive correlation was noted between Ki67 LI and mitotic index in tumor proper (r = 0.263, P = 0.033) and proliferative margin (r = 0.364, P = 0.003). Conclusion: Mitotic index, a rapid and affordable tool for assessing cellular proliferation, becomes more relevant and practically effective when used in conjunction with Ki-67. Combined analysis of the two indices can be useful in the early diagnosis of possibly malignant lesions and in predicting tumor behavior.